The success rate of dental implant placement using sinus lift vertical approach technique without bone grafting: Scoping review - Oktariani, Anisa Nabilah; Hardianto, Andri; Putri, Dian Maifara (Padjadjaran Journal of Dental Researchers and Students, 2026)
ABSTRACTIntroduction: Dental implants are a treatment aimed at restoring the function and aesthetics of teeth in the oral cavity. They must have stable integrity in the local bone where they are placed. Sinus lift vertical approach without bone graft is a procedure that can be used to place dental implants in cases of maxillary atrophy. The objective is to map the available evidence regarding the success of dental implant placement using the sinus lift vertical approach without bone graft. Methods: This study was conducted using a scoping review method in accordance with PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analytic for Scoping Review) based on predetermined inclusion and exclusion criteria. Articles were obtained from three databases, namely PubMed, Scopus, and Cochrane focusing on randomized controlled/clinical trial (RCT) study designs published between 2014 and 2023.  The analyzed data included the year of publication, study design, number of patients, patient characteristics, implant length, follow-up duration, lifting technique, outcome measurement method, implant survival rate, bone height gain, other success indicators, and complications. Results: Nine articles were included in the review (six two-group RCTs and three three-group RCTs). The results showed a high implant survival rate, ranging from 94.1%-100% and bone height gain up to 4.1 ± 1.0 mm. Reported complications included mucositis and perforation of the mucous membrane. Conclusion: The sinus lift vertical approach without bone graft can be a valid technique and provides good results for dental implant placement in atrophic maxillary conditions requiring bone height gain of less than 4 mm.KEYWORDS: dental implants, sinus lift vertical approach, bone grafting, bone height gain, implant survivalTingkat keberhasilan pemasangan implan gigi dengan teknik sinus lift vertical approach tanpa menggunakan bone graft: Scoping reviewABSTRAKPendahuluan: Implan gigi merupakan perawatan yang berfungsi untuk mengembalikan fungsi dan estetik gigi di dalam rongga mulut.  Implan gigi harus memiliki integritas yang stabil pada tulang lokal tempat implan gigi dipasang. Sinus lift vertical approach tanpa menggunakan bone graft merupakan salah satu prosedur yang dapat digunakan untuk memasang implan gigi pada kasus atrofi maksila. Tujuan untuk menganalisis tingkat keberhasilan pemasangan implan gigi dengan teknik sinus lift vertical approach tanpa menggunakan bone graft. Metode: Penelitian dilakukan dengan metode scoping review sesuai dengan PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analytic for Scoping Review) berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Artikel berasal dari tiga database, yaitu PubMed, Scopus, dan Cochrane dengan desain penelitian randomized controlled/clinical trial (RCT) yang terbit dari tahun 2014-2023. Data yang dianalisis berupa tahun publikasi, desain penelitian, jumlah pasien, karakteristik pasien, panjang implan, durasi follow-up,  teknik lifting, metode pengukuran hasil, implant survival rate, bone height gain, indikator keberhasilan lainnya, dan komplikasi. Hasil: Sembilan artikel dimasukkan setelah analisis, terdiri dari 6 artikel RCT two groups dan 3 artikel RCT three groups. Artikel yang ditinjau melaporkan implan gigi yang dipasang menggunakan teknik sinus lift vertical approach tanpa menggunakan bone graft dapat memberikan hasil bone height gain mencapai 4,1 ± 1,0 mm dan implant survival rate berkisar antara 94,1-100%. Komplikasi yang mungkin terjadi setelah prosedur ini adalah mukositis dan perforasi membran mukosa. Simpulan: Sinus lifting vertical approach tanpa menggunakan bone graft dapat menjadi teknik yang valid dan memberikan hasil yang baik untuk pemasangan implan gigi pada kondisi atrofi maksila yang memerlukan penambahan tulang tidak lebih dari 4 mm.KATA KUNCI: implan gigi, elevasi membrane sinus, cangkok tulang, pertambahan tinggi tulang, kelangsungan hidup implant